High Resolution Melting Analysis for Rapid Detection of PIK3CA Gene Mutations in Bladder Cancer: A Mutated Target for Cancer Therapy - Ousati Ashtiani, Zahra; Mehrsai, Abdol Rasoul; Pourmand, Mohammad Reza; Pourmand, Gholam Reza (Urology journal, 2018)
PIK3CA gene mutations have clinical importance and their presence is associated with therapy response. They are also considered as a molecule for targeted therapy. As regards to their importance, genetic variation within a population as well as among different populations, this study was conducted to detect common mutations of exons 9 and 20 and other probable mutations in PIK3CA gene as well as their frequencies in Iranian bladder cancer patients. Paired tumor and adjacent normal tissues samples were obtained from 50 bladder cancer patients. Mutations of PIK3CA gene were detected using High Resolution Melting (HRM) analysis which is ahighly sensitive, repeatable, rapid, and cost-effective technique. To determine the precision of the HRM analysis, Sanger sequencing analysis was used. The result showed that mutations were present in 10% (5/50) of the subjects. The majority of these cases (4/5) had the mutation(s) in exon 9, spanning over five different mutations, among which three of them were actually novel mutations. Further analysis showed that 2 cases had simultaneous mutations for exon 9. In addition to novel mutations, the PIK3CA mutation rate observed in Iranian bladder patients was not as frequent as previous reports and COSMIC. HRM can be used as a rapid and sensitive method for mutation screening. Dysregulation of PIK3CA gene in bladder cancer reveals its potentials as a mechanistic link for cancer development, which in turn suggests its special use in interventional studies for targeted therapy.